2018
DOI: 10.3389/fneur.2018.00056
|View full text |Cite
|
Sign up to set email alerts
|

Light and Cognition: Roles for Circadian Rhythms, Sleep, and Arousal

Abstract: Light exerts a wide range of effects on mammalian physiology and behavior. As well as synchronizing circadian rhythms to the external environment, light has been shown to modulate autonomic and neuroendocrine responses as well as regulating sleep and influencing cognitive processes such as attention, arousal, and performance. The last two decades have seen major advances in our understanding of the retinal photoreceptors that mediate these non-image forming responses to light, as well as the neural pathways an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(132 citation statements)
references
References 234 publications
(248 reference statements)
4
111
0
3
Order By: Relevance
“…31 Alertness and arousal are known to affect cognitive performance. 32,33 Previous studies also showed that better work performance was found along with enhanced alertness under high CCT lighting condition with more blue components, 5,34 which aligns with our finding. These nonimage forming effects of blue light are mainly regulated by melanopsin illuminance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…31 Alertness and arousal are known to affect cognitive performance. 32,33 Previous studies also showed that better work performance was found along with enhanced alertness under high CCT lighting condition with more blue components, 5,34 which aligns with our finding. These nonimage forming effects of blue light are mainly regulated by melanopsin illuminance.…”
Section: Discussionsupporting
confidence: 92%
“…It implies that more severe visual fatigue produced under blue‐enriched light does not deteriorate cognition performance, which may be related to the alertness or arousal modulated by blue light . Alertness and arousal are known to affect cognitive performance . Previous studies also showed that better work performance was found along with enhanced alertness under high CCT lighting condition with more blue components, which aligns with our finding.…”
Section: Discussionsupporting
confidence: 91%
“…22 The anterior hypothalamus comprises among other nuclei the suprachiasmatic nucleus, which serves as a key integrator between environmental stimuli and internal metabolic and endocrinological factors and has long been hypothesized to play a key role in migraine attack generation. 12,13,23 When looking at the time course of contrast estimates at the various points of scanning, it is also noteworthy that hypothalamic activation rises above the interictal level only within the last 48 hours before headache onset and appears to fall back to that level during the headache phase. This evidence of a cycling behavior on a hypothalamic level mirrors the previously reported cycling of the spinal trigeminal nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of blue light on cognitive processes may be considered in terms of complex interactions between circadian, sleep, and arousal factors. Particularly, blue light, through NIF system, can either act directly on neuronal system and thus on alertness and behavior, or indirect effects may occur due to disrupted entrainment of circadian system and/or sleep (Fisk et al, 2018). Therefore, the effects of changed blue light condition can be interpreted in terms of different mechanisms.…”
Section: Discussionmentioning
confidence: 99%